Solution;
Given the equation of the curve is;
"x^2+3xy+y^2=5"
At "P_0(x_0,y_0)" When "x_0=1"
Differentiate as follows;
"2x+3y+3x\\frac{dy}{dx}+2y\\frac{dy}{dx}=0"
Group;
"(3x+2y)\\frac{dy}{dx}=-(2x+3y)"
"\\frac{dy}{dx}=\\frac{-(2x+3y)}{3x+2y}"
Since "x_0=1" ,by direct substitute into the equation,find values of y.
"x^2+3xy+y^2=5"
"(1^2)+3(1)y+y^2=5"
"y^2+3y-4=0"
"y^2-y+4y-4=0"
"y(y-1)+4(y-1)=0"
Hence ;
"y=1 or -4"
Use y=1 because at y=-4,the gradient of the equation is not equal to 1.
So the point "P_0(x_0,y_0)=P_0(1,1)"
"\\frac{dy}{dx}(1,1)=\\frac{-(2+3)}{3+2}=-1"
The equation of the normal to curve is ;
"(x-1)=1(y-1)"
"x-y=0"
This is the required solution.
Comments
Leave a comment